MYNd&CO (Mindfulness, Yoga, Nutrition, development & Coaching, and Osteopathy) randomized controlled trial for a positive psychophysical experience in pregnancy and after birth: a study protocol - Giovannini, Niccolò; Cetera, Giulia Emily; Ercolino, Carolina; Miozzo, Monica Rosa; Parazzini, Fabio; Ferrazzi, Enrico Maria; Manzotti, Andrea; Colaceci, Sofia (Acta Biomedica Atenei Parmensis, 2021)
Background and aim: The medicalisation of birth pathway may negatively impact on women’s empowerment, enhancing distress even in cases of healthy pregnancies. We have built a program which is comprised of Mindfulness, Yoga, Nutrition, development & Counselling, Coaching, antenatal classes, and Osteopathic treatment (MYNd&CO). Methods: This study is a randomized controlled trial involving low-risk pregnant women. They will be randomized to the experimental (MYNd&CO intervention plus standard care) or control group (standard care). The primary (general health and wellbeing, maternal distress) and secondary outcome measures (urinary incontinence, sexual problems, and physical wellbeing) will be assessed via questionnaires at baseline and 6 months after childbirth. The independent-samples t-test and Chi-square will be used to detect changes in the outcomes between intervention and control group. Discussion: The trial is expected to increase knowledge about the effectiveness of a holistic approach in low-risk pregnant women, in terms of obstetrical and psychophysiological outcomes.